ANALYTICAL REVIEW OF THE METHODS OF INSPECTION AND PLANNING THE REPAIR OF REINFORCED CONCRETE AND METAL BRIDGES (Collection of scientific works «Modern structures of metal and wood», 2024)
The  article  analyzes  the  factors  that  affect  the  service  life  of  bridge  structures. Based on the practical recommendations of foreign project institutions, the principles of monitoring the state of bridges and their maintenance were determined. The expediency of survey strategies for the expansion of domestic regulatory recommendations for bridge repair and maintenance has been clarified.  General  scientific  methods  are  used,  such  as  analysis,  systematization,  generalization, comparison.  The  article  examines  the  current  norms  and  standards  of  Ukraine,  the  materials  of international legislative documents in the field of road infrastructure. Remote analysis of objects: scientific publications and articles became the empirical basis for conducting scientific work. The article examines the peculiarities of bridge inspection implementation and maintenance planning. The main decisions regarding effective management of the network of bridge structures and control of their operational condition are outlined. A number of Ukrainian and foreign sources dealing with this problem have been studied. In order to create an idea about the procedure of repair work, the world experience of the procedure for carrying out bridge inspections, the systematization of assessing the condition and urgency of repairs, the level of inspection and its periodicity, and also analyzed  the  methods  aimed  at  increasing  the  durability  of  specific  elements  of  bridges  were studied. It was found that a rational and systematic inspection of the condition of bridge structures is a cost-effective way to ensure its functionality.